Pengaruh Literasi Keuangan Terhadap Penggunaan Pembayaran Digital Pada Mahasiswa Pendidikan Ekonomi FKIP Universitas Riau - Tiara Dzakiyah; Mujiono Mujiono; Hardisem Syabrus (Jaanur Elbarik Indonesia, 2026)
This study aims to analyze the influence of financial literacy on the use of digital payments among Economics Education students at the Faculty of Teacher Training and Education, University of Riau. This study employs a descriptive method with a quantitative approach. The study population consists of Economics Education students from the 2022–2024 cohorts, with a sample of 78 respondents determined using the Slovin formula and purposive sampling. Data collection was conducted through the distribution of a questionnaire using a Likert scale. The results indicate that financial literacy has a positive and significant effect on the use of digital payments among students. Students with a high level of financial literacy tend to be better able to understand, manage, and utilize digital payment services wisely, effectively, and responsibly in their daily transactions. The high usage of digital payments also indicates that students have been able to adapt to developments in financial technology in the digital era. Furthermore, financial literacy is a key factor supporting more purposeful financial behavior in the use of digital payment services